Interfacial mechanism of sulfonic acid-doped polyaniline/ cotton fabric for maximized electrical properties and tailored surface functionality - Parvez, Md. Shohan; Rahman, Md Mustafizur; Samykano, Mahendran; Maleque, M. A. (Elsevier, 2025)
Wearable electronics are being revolutionized by conductive polymers like polyaniline (PANI) due to their excellent optical and electrical properties. However, its processability, solvent selection, and establishment of stable synthesis protocols have hindered widespread applications. This study aims to investigate PANI polymerization on cotton fabrics using p-toluene sulfonic acid (pTSA) as a dopant, aniline as a monomer, and ammonium persulfate (APS) as an oxidant. This research elucidates the interfacial mechanism and formulates a relationship among synthesis parameters governing electrical properties for high-performance e-textile applications. The significance lies in developing a robust strategy to conformally coat flexible cotton with highly conductive PANI for next-generation wearable devices. A Box-Behnken response surface methodology systematically optimized critical parameters - aniline monomer, oxidant, and pTSA dopant concentrations. Comprehensive characterizations were performed, including FTIR, FESEM, EDX, XRD, UV-Vis, and measurement of sheet resistance. The quadratic model fitted the data excellently (R2 = 0.9899, F = 75.95, p < 0.0001), validating the optimization approach. The optimized conditions (0.3M aniline, 0.38M APS, 0.6M pTSA) facilitated a uniform, conformal PANI coating with the desirable emeraldine salt oxidation state, minimizing the sheet resistance to 2.60 kΩ/sq. This 80% reduction compared to non-optimized syntheses dramatically enhanced charge transport within the conductive fabrics. In conclusion, this rational design strategy successfully tailored the sulfonic acid-PANI synthesis to maximize the electrical performance of cotton-based e-textiles. The optimized composites are promising for flexible energy storage, sensors, electromagnetic shielding, electro-thermal devices, and other wearable applications. Further work explores innovative PANI nanostructures and industrial scale-up feasibility.